Factors related to the incorrect use of hospital uniforms by medical students - Orozco Delgado, Diego (2025)
Introduction: Health worker’s clothing, including medical students, is often contaminated by pathogens causing high-mortality infections and long hospital stay. Hence, wearing medical attire outside the hospital setting is a breach of the current hospitals’ biosafety standards. Objective: To determine the prevalence of incorrect use of hospital uniforms and to establish its relationship with the degree of knowledge of medical students about biosafety regulations and their self-perception when using them outside the hospital. Methods: Observational, analytical-cross-sectional study in medical students to identify the prevalence of incorrect use of hospital uniforms and factors related to this practice through a CAPs survey. Results: 79.89% of the participants wore medical uniforms outside pratice hours and outside the hospital, even though they were aware that this is a breach of biosafety regulations. 31.2% of the participants liked the fact that by wearing their uniform outside the hospital they were recognized as health personnel. Discussion: Ecuador does not have precise data about the rigorous application of biosecurity measures in hospitals. The regularization of the use of hospital uniforms outside the hospital should be a priority for health systems, due to the increase in infectious diseases transmitted by contact. Conclusions:  Medical students are aware of the infectious potential of hospital uniforms, but their use in out-of-hospital environments is still a frequent practice.